IAponskie istorii - Sokurov, Aleksandr (Russia : Bereg, Nadezhda)
Three film novellas by Alexander Sokurov, tied together by the author's reflections on Japanese culture. EASTERN ELEGY (1996), 45 min.: Sokurov's first documentary about Japan, the film is composed of a series of interviews with elderly residents of Japan. A HUMBLE LIFE (1997), 75 min.: This documentary focuses on the day-to-day life of an elderly Japanese woman, who lives in an isolated part of Japan. DOLCE... GENTLY (1999), 60 min.: The film is dedicated to the famous Japanese writer Tosio Simao, who died in 1986. Sokurov intrviews his elderly wife and ailing daughter, and in the process tries to capture the spirit of ancient Japanese customs and rituals.
Duration: 03:02:00
With voice-over in Russian
Keywords: Fiction films